Semisynthetic Derivatives of Selected Amaryllidaceae Alkaloids as a New Class of Antimycobacterial Agents - Maafi, Negar; Mamun, Abdullah Al; Janďourek, Ondřej; Maříková, Jana; Breiterová, Kateřina; Diepoltová, Adéla; Konečná, Klára; Hošťálková, Anna; Hulcová, Daniela; Kuneš, Jiří; Kohelová, Eliška; Koutová, Darja; et al. (Molecules (Basel, Switzerland), 2021)
The search for novel antimycobacterial drugs is a matter of urgency, since tuberculosis is still one of the top ten causes of death from a single infectious agent, killing more than 1.4 million people worldwide each year. Nine Amaryllidaceae alkaloids (AAs) of various structural types have been screened for their antimycobacterial activity. Unfortunately, all were considered inactive, and thus a pilot series of aromatic esters of galanthamine, 3-O-methylpancracine, vittatine and maritidine were synthesized to increase biological activity. The semisynthetic derivatives of AAs were screened for their in vitro antimycobacterial activity against Mycobacterium tuberculosis H37Ra and two other mycobacterial strains (M. aurum, M. smegmatis) using a modified Microplate Alamar Blue Assay. The most active compounds were also studied for their in vitro hepatotoxicity on the hepatocellular carcinoma cell line HepG2. In general, the derivatization of the original AAs was associated with a significant increase in antimycobacterial activity. Several pilot derivatives were identified as compounds with micromolar MICs against M. tuberculosis H37Ra. Two derivatives of galanthamine, 1i and 1r, were selected for further structure optimalization to increase the selectivity index.
Keywords: Amaryllidaceae; Mycobacterium tuberculosis; cytotoxicity; tuberculosis; buňky Hep G2; alkaloidy amarylkovitých; Anti-Bacterial Agents; mikrobiální testy citlivosti; Humans; Microbial Sensitivity Tests; Hep G2 Cells; 3-O-methylpancracine; analogues; antimycobacterial activity; galanthamine; Amaryllidaceae Alkaloids; lidé; antibakteriální látky